An investigation into the effects and implications of gamma radiation on organic matter, crude oil, and hydrocarbon generation - Kelly, Logan (Kansas State University, 2014)
The current model of hydrocarbon generation involves the thermogenic maturation of organic material as a consequence of burial. This process only considers energy generated from temperature increase due to burial. The majority of organic rich source beds contain high concentrations of radioactive elements, hence the energy produced from radioactive decay of these elements should be evaluated as well. Previous experiments show that α-particle bombardment can result in the generation of hydrocarbons from oleic acid. This study investigates the effects of γ-rays in a natural petroleum generating system. In order to determine the effects of γ-rays, experiments were conducted using cesium-137 as the γ-ray source at the KSU nuclear facilities to irradiate crude oil and organic material commonly found in petroleum systems. The samples were then analyzed using Fourier Transform Infrared Spectroscopy (FTIR) and Rock-Eval pyrolysis to determine changes in the samples. The FTIR results demonstrated that γ-radiation can cause the lengthening and/or shortening of hydrocarbon chains in crude oils, the dissociation of brine (H2O (aq)), the production of free radicals, and the production of various gases. These changes that come from γ-radiation hold the possibilities to distort the configuration of organic molecules, dissociate molecular bonds, and trigger oxidation-reduction reactions, all of which could provide an important step to the onset of dissociation necessary to create hydrocarbons in petroleum systems. Further understanding the effects of γ-radiation in hydrocarbons systems could lead to more information about the radiolytic processes that take place. This could eventually lead to further understanding of oil generation in organic-rich source beds.
Keywords: Geology; Petroleum geology; Geochemistry; Radioactive decay; Hydrocarbon maturation; Geochemistry (0996); Geology (0372); Petroleum Geology (0583)